2021
DOI: 10.3389/fnbeh.2021.780500
|View full text |Cite
|
Sign up to set email alerts
|

Self-Administration of Entactogen Psychostimulants Dysregulates Gamma-Aminobutyric Acid (GABA) and Kappa Opioid Receptor Signaling in the Central Nucleus of the Amygdala of Female Wistar Rats

Abstract: Male rats escalate intravenous self-administration of entactogen psychostimulants, 3,4-methylenedioxymethcathinone (methylone) and 3,4-methylenedioxymethamphetamine (MDMA) under extended access conditions, as with typical psychostimulants. Here, we investigated whether female rats escalate self-administration of methylone, 3,4-methylenedioxypentedrone (pentylone), and MDMA and then studied consequences of MDMA and pentylone self-administration on GABAA receptor and kappa opioid receptor (KOR) signaling in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Additional studies are needed to identify MOR-sensitive GABAergic inputs in the CeA. Like MORs, KOR activation inhibits GABA release in CeA in rats ( Przybysz et al, 2017 ) and KORs may also tonically inhibit GABA release ( Gilpin et al, 2014 ; Bloodgood et al, 2021 ; Khom et al, 2021 ). Similarly, DORs also inhibit GABA release in the CeA, but there is evidence for species differences.…”
Section: Amygdalamentioning
confidence: 99%
“…Additional studies are needed to identify MOR-sensitive GABAergic inputs in the CeA. Like MORs, KOR activation inhibits GABA release in CeA in rats ( Przybysz et al, 2017 ) and KORs may also tonically inhibit GABA release ( Gilpin et al, 2014 ; Bloodgood et al, 2021 ; Khom et al, 2021 ). Similarly, DORs also inhibit GABA release in the CeA, but there is evidence for species differences.…”
Section: Amygdalamentioning
confidence: 99%
“…Although work with conditioned place preference (CPP) has been reported with a number of synthetic cathinones (see Cheong et al, 2017; Gannon et al, 2017; Gatch et al, 2015; King, Wakeford, et al, 2015; King, Wetzell, et al, 2015; Marusich et al, 2016; Nelson et al, 2017; Risca et al, 2020), such work has not been assessed with eutylone. However, work with methylone (Karlsson et al, 2014; Miyazawa et al, 2011) has shown its ability to support place preference conditioning and eutylone’s structural isomers induce locomotor activation (Glatfelter et al, 2021; Javadi-Paydar et al, 2018; López-Arnau et al, 2012; Saha et al, 2019), substitute for cocaine and amphetamine (among other drugs of abuse) in drug discrimination assessments (Dolan et al, 2018; Gatch et al, 2019), and support intravenous self-administration (IVSA; Dolan et al, 2018; Javadi-Paydar et al, 2018; Khom et al, 2021; Lai et al, 2022), indicating their abuse potential.…”
mentioning
confidence: 99%
“…All rats were housed in a temperature- and humidity-controlled room on a 12 h light/dark cycle with food and water available ad libitum. Alcohol-dependent rats (average blood alcohol level 172.68 ± 17.4 mg/dL at time of sacrifice) were generated by exposure to alcohol vapor daily (14 h alcohol vapor; 10 h air vapor) for 5–7 weeks [ 30 , 48 , 49 , 50 ] Female ( N = 6) and male ( N = 6) Wistar rats (Charles River, Raleigh, NC, USA) weighed on average 253.17 ± 12.7 g and 387.67 ± 24.5 g, respectively, at time of sacrifice. All procedures and care were conducted in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals and were reviewed and approved by the Institutional Animal Care and Use Committee of The Scripps Research Institute.…”
Section: Methodsmentioning
confidence: 99%